Volunteer RR® corn management in roundup ready® soybean-corn succession system - PETTER,F.A. (2015)
The present study evaluated the effects of cover crops (Pennisetum glaucum, Crotalaria spectabilis and Urochloa ruziziensis) associated with the application of herbicides {glyphosate; (glyphosate + haloxyfop-R); (glyphosate + fluazifop-p-butyl); (glyphosate + imazethapyr) and (glyphosate + imazaquin)} in soybean desiccation management for volunteer RR® corn control. The experiment was conducted under field conditions at Sinop-MT, during the 2013/2014 crop season, in a randomized complete blocks design with factorial scheme and four replications. The following parameter were evaluated: dry matter of cover crops and ground coverage rate, control of volunteer RR® corn present at the time of desiccation, dry matter, height and intoxication level on soybean plants caused by herbicides at 7, 14 and 28 days after emergence (DAE), control of volunteer RR® corn derived from emergence fluxes subsequent to desiccation management and soybean yield. The joint application of (glyphosate + haloxyfop-R) provided the best level of volunteer RR® corn control present at the time of desiccation. Satisfactory control (80%) of volunteer corn was obtained with the application of (glyphosate + imazethapyr). This treatment displayed an additional residual effect of imazethapyr, which efficiently controled volunteer RR® corn derived from fluxes subsequent to desiccation management, especially in treatments performed under U. ruziziensis straw. None of the herbicides used in desiccation management caused any significant effect on dry matter, height and phytotoxicity of soybean plants at 7, 14 and 28 DAE nor on grain yield.